Rocket Media Development A Cardboard Waste Race to Improve the Cognitive Abilities of 4-5 Year Old Children in Kindergarten - Ismi Nurkhasanah; Yusuf, Muhammad; Isnaini Nur Azizah (CV. Creative Tugu Pena, 2024)
The aim of this research is to develop innovative learning media made from cardboard waste, namely Rocket. Race, to improve the cognitive abilities of children aged 4–5 years in Qur'an Kindergarten Ma'arif Sumber Rejeki. The background of this research is based on the results of observations that show that most children are still in the